Analysis of The Structure and Composition of Mangrove Vegetation Types in Induha Latambaga Village, Kolaka District - Sutriani Kaliu; Saparuddin Saparuddin; M. Alkadri; Erfina Erfina; Nasarudin Nasarudin; Djunarlin Tojang (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mangroves are plants typical of tidal boundaries, beaches and around river mouths. Mangrove vegetation in Induha Village is spread along the coast. Information regarding the structure and composition of mangrove vegetation is still lacking, so research is needed. This research was conducted to determine the structure and composition of mangrove vegetation in Induha Latambaga Village, Kolaka Regency. This study used the point centered sampling method and the observed parameters were seedlings, saplings and trees as well as the composition of the mangrove vegetation. The results showed that Rhizophora apiculata had the highest relative dominance in seedlings (42.13%), saplings (57.50%) and trees (38.31%). Relative frequency in seedlings (35%), saplings (45%) and trees (34.5%). Relative LBA for seedlings (50%), saplings (84.83%) and trees (52.34%). KR in saplings (57.2%) and trees (35.5%), as well as IVI in seedlings (136.1%), saplings (248%) and trees (148.1%). Vegetation composition consisted of 3 families (Rhizophoraceae, Acanthaceae and Sonneratiaceae) and 4 species (R. apiculata, R. mucronata, R. stylosa and B. cylindrical). Environmental factors in Induha Village support the survival of mangroves, especially Rhizophora apiculata.